Polymorphonuclear neutrophil chemotaxis under aerobic and anaerobic conditions. - Casciato, D A (1978)
The motility of human polymorphonuclear neutrophils was studied in vitro under aerobic and anaerobic conditions. Chemotactic factors were generated from plasma with immune complexes or with whole bacteria (Staphylococcus aureus, Escherichia coli, and Bacteroides fragilis). Chemotaxis induced by chemotactic factors generated from immune complexes was identical under both conditions. However, chemotaxis utilizing chemotactic factors generated from bacteria was markedly depressed under anaerobic conditions. Mean random tubemoltility was not significantly different under aerobic and anaerobic conditions. These data indicate that different metabolic pathways may be involved in polymorphonuclear neutrophil movement. Some of these pathways require oxygen (chemotaxis in response to factors generated by bacteria in plasma), whereas others do not (random tube migration and chemotaxis in response to factors generated by immune complexes in plasma). These observations may be important in the induction of inflammatory responses within hypoxic tissues.